Avaliação da evasão em uma Instituição de Ensino Superior do Rio Grande do Norte - Brasil, Rosemary Feitoza (2015)
The evasion in the Brazilian college education is a historical problem in the education process of democratization, reflecting the different layers of Brazilian society. Onerous, doubly society, both in relation to the waste of resources invested in education, as in people who are under-utilized during the duration of the course. The immediate impact of this inefficiency is the low number of students who can complete the course in which they were selected, as well as relative deficiency in workers entering the labor market. This study aims to evaluate quantitatively, in a ten-year period, evasion in courses offered by the Federal Rural University of the Semi-Arid Campus Mossoró. The evasion proved oscillating and growing throughout the semesters analyzed in most of the studied areas of knowledge addressed in public university. From the results of quantitative analysis can be studied methodologies for contributing to the permanence of the student in the course of origin, or understand and minimize the factors that cause your evasion. After all, college education in Brazil is seen under an optical "where many are called but few are chosen